THE CORRELATIONAL STUDY BETWEEN STUDENTS INTEREST AND THE STUDENTS READING COMPREHENSION - Yunus, Reski Yusrini Islamiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
The objectives of the study are to find out significant correlation between reading interest through the studentsâ reading comprehension. In this research, the researcher used quantitative method by Pearson correlation product moment. There are four variables in this research. Studentsâ interest as prediction variable and Reading comprehension as criterion variable, the technique of collecting data was by using a questionnaire and test. The questionnaire consists of 20 items and 46 items of reading comprehension. The object of study is 30 students from class D at the third semester. After getting the score of the studentsâ interest and reading comprehension, the data were statistically computed to find out the correlation between those variables. From the calculation by using product moment formula, it was found out that the mean scores of the studentâs interest 75.53. The mean of the scores of the studentsâ reading comprehension is 5.53. The result of applying the variable rx1y (ro) distribution shows that the coefficient correlation between students interest and reading comprehension is 0.919 or 91.9% means that there was very strong correlation. The degree of significance 5% is 0,000. It means p is smaller than 0.05 (0.05 < 0.000). So, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. The conclusion of this research is there is a significant correlation between students âinterest and their reading comprehension.